Epidemiology of Supracondylar Fractures of the Humerus in Children - Santos, Isadora Azarias; Cruz, Mário Augusto Ferreira; Souza, Rafael Chaves; Barreto, Lucas Vinícius da Fonseca; Monteiro, Aécio Freire; Rezende, Luis Guilherme Rosifini Alves (ARCHIVES OF HEALTH INVESTIGATION, 2024)
Background: Supracondylar fracture of the humerus are the second most common fracture in pediatric patients. There are few studies concerning their epidemiology in Brazil. This study aims to assess the clinical and epidemiological characteristics of supracondylar fractures of the humerus in children managed at a tertiary-level hospital within the Brazilian Unified Health System (translation for SUS - Sistema Público de Saúde). Methods: This retrospective study included patients younger than 13 years diagnosed with supracondylar fracture of the humerus assisted at an urgent and emergency referral unit of the Unified Health System from June 2022 to July 2023. The statistical analysis used R software version 4.0.4 with a significance level set at 0.05 using descriptive and inferential statistics. Results: 197 children with mean age of 5.4 years (2.4) were diagnosed with a supracondylar fracture of the humerus. The highest temporal incidence occurred in December, being 56.9% male patients, 81.3% identified as African American, and 51.8% had a fracture on the left side. The most prevalent cause for the fracture was a fall from standing height on the outstretched hand. At least 95% of the patients had extension fractures, and the distribution by Gartland classification was: I, 36.7%; II, 26.2%; III, 30.9%; and IV, 6.3%. Three patients had a neurological injury. All patients with III and IV fractures, as well as those with flexion fractures, underwent surgery. However, of the 50 patients with grade II fractures, 11 underwent surgery, and 39 managed with nonoperative methods. We observed an association between the fracture severity, and fall height, neurological impairment, and management received. Conclusion: Targeted education efforts and interventions can prevent the occurrence of supracondylar fractures in our region at the northeast side of the country.